Mechanical, structural, and optical properties of PEALD metallic oxides for optical applications - Shestaeva, Svetlana; Bingel, Astrid; Munzert, Peter; Ghazaryan, Lilit; Patzig, Christian; Tuennermann, Andreas; Szeghalmi, Adriana (Applied Optics, 2017)
Structural, optical, and mechanical properties of Al2O3, SiO2, and HfO2 materials prepared by plasma-enhanced atomic layer deposition (PEALD) were investigated. Residual stress poses significant challenges for optical coatings since it may lead to mechanical failure, but in-depth understanding of these properties is still missing for PEALD coatings. The tensile stress of PEALD alumina films decreases with increasing deposition temperature and is approximately 100 MPa lower than the stress in thermally grown films. It was associated with incorporation of -OH groups in the film as measured by infrared spectroscopy. The tensile stress of hafnia PEALD layers increases with deposition temperature and was related to crystallization of the film. HfO2 nanocrystallites were observed even at 100°C deposition temperature with transmission electron microscopy. Stress in hafnia films can be reduced from approximately 650 MPA to approximately 450 MPa by incorporating ultrathin Al2O3 layers. PEALD silica layers have shown moderate stress values and stress relaxation with the storage time, which was correlated to water adsorption. A complex interference coating system for a dichroic mirror (DCM) at 355 nm wavelength was realized with a total coating thickness of approximately 2 μm. Severe cracking of the DCM coating was observed, and it propagates even into the substrate material, showing a good adhesion of the ALD films. The reflectance peak is above 99.6% despite the mechanical failure, and further optimization on the material properties should be carried out for demanding optical applications.
CRIS-Team Scopus Importer:2023-04-20